Antibacterial Activity of Zanthoxylum Armatum (Timur) on Gram Positive Bacteria and Gram Negative Bacteria (Research Journal of Padmakanya Multiple Campus, 2023)
Zanthoxylum armatum is commonly known as Timur which is a major indigenous spice of Nepal. The objective of this research work is to determine the antibacterial activity of Z. armatum. The fresh fruits seeds of Z. armatum were collected from Pyuthan District of Nepal. About 25 gram of seeds were grinded to make powder and mixed with 500 ml ethanol for ethanol extraction. Then, extraction was separated by filtration and left for time until residue obtained. The residue obtained was mixed with DMSO (10%) and diluted to 1% and 10% dilution. Agar well diffusion method was done for studying antimicrobial activity for the Gram positive bacteria (Staphylococcus aureus and Bacillus spp.,) and Gram negative bacteria (Escherichia coli, Klebsialla pneumonia, Salmonella Typhi and Shigella dysenteriae). For the quality control of test, antimicrobial activity of Z. armatum was also done for Staphylococcus aureus (ATCC: 25923) and Escherichia coli (ATCC: 25922) along with positive control (Oflaxacin) and negative control (10% DMSO). Among different concentration of 1%, 10%, and 100% of ethanol extract of Z. armatum, 10% and 100% of ethanol extract were found to be effective for both Gram positive bacteria and Gram negative bacteria. From this study, it was concluded that antibacterial activities of Z. armatum was found to be effective.